2020
DOI: 10.21203/rs.2.20347/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pleiotropic effect of the ABCG2 gene in gout: involvement in serum urate levels and progression from hyperuricemia to gout

Abstract: Background The ABCG2 Q141K ( rs2231142 ) and rs10011796 variants associate with hyperuricaemia (HU). The effect size of ABCG2 rs2231142 on urate is ~60% that of SLC2A9, yet the effect size on gout is greater. We tested the hypothesis that ABCG2 plays a role in the progression from HU to gout by testing for association of ABCG2 rs2231142 and rs10011796 with gout using HU controls. Methods We analysed 1,699 European gout cases and 14,350 normourciemic (NU) and HU controls, and 912 New Zealand (NZ) Polynesian … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
2
4
0
Order By: Relevance
“…A similar pattern of hyperuricemia has been reported in the rs475688, rs3825016, and rs11726117 polymorphisms of the SLC22A12 gene encoding for URAT1 which results in renal hypouricemia type 1 [41,42]. A similar outcome has been observed with the rs2231142 single nucleotide polymorphism of the BCRP gene encoding for ABCG2 in addition to defective intestinal urate excretion [43,44]. Rare cases of OAT4 or OAT10 gene mutations have been identified in the literature as potential etiological factors for hyperuricemia [45,46].…”
Section: Ua and Genetic Variationssupporting
confidence: 65%
“…A similar pattern of hyperuricemia has been reported in the rs475688, rs3825016, and rs11726117 polymorphisms of the SLC22A12 gene encoding for URAT1 which results in renal hypouricemia type 1 [41,42]. A similar outcome has been observed with the rs2231142 single nucleotide polymorphism of the BCRP gene encoding for ABCG2 in addition to defective intestinal urate excretion [43,44]. Rare cases of OAT4 or OAT10 gene mutations have been identified in the literature as potential etiological factors for hyperuricemia [45,46].…”
Section: Ua and Genetic Variationssupporting
confidence: 65%
“…ABCG2, an ATP-driven efflux pump, has a significant role in urate secretion in the proximal tubule and intestine. In addition to SLC2A9 and ABCG2, GWASs of patients with gout have identified a few other gout risk loci, which were consistent with those found in GWASs of HUA [14][15][16] (Table 1).…”
Section: Differences In Genetic Features Between Hua and Goutsupporting
confidence: 71%
“…Further study revealed that macrophage-derived platelet-activating factor (PAF) is involved in the non-inflammatory phagocytosis of MSU crystals by human blood monocyte-derived differentiated macrophages [36] . PAF is regarded as a potent mediator of immune responses that regulates various processes, including cytokine release and phagocytosis [1,[15][16] . When stimulated with MSU crystals, in vitro differentiated macrophages were found to secrete PAF, whereas this secretion was absent in immature monocytes under the same stimulation.…”
Section: Noninflammatory Uptake Of Msu Crystals By Mature Macrophagesmentioning
confidence: 99%
“…(7) The ABCG2 gene is strongly associated with SU levels, early-onset gout, and the progression from HU to gout. (41)(42)(43) The encoded protein, ATP-binding cassette superfamily G member 2 (ABCG2), is expressed in both the kidney and liver and functions as a urate e ux transporter. The genetic polymorphism rs2231142 (G>T) in ABCG2 leads to Glu141Lys amino acid change, which results in a reduced ABCG2mediated urate e ux activity and in ammation dysregulation via augmented IL-8 release (Table 1).…”
Section: Discussionmentioning
confidence: 99%